IDENTIFIKASI LARVA DAN NYAMUK DI SEKARJAYA BATURAJA KABUPATEN OGAN KOMERING ULU SUMATERA SELATAN INDONESIA SEBAGAI LANGKAH AWAL PENGENDALIAN FLAVIVIRUS (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2019)
ABSTRACT Background: vector and disease data from the Flaviviridae family of Ogan Komering Ulu Regency, South Sumatra, Indonesia, are not known, so that larvae and mosquitoes are found in Sekarjaya Baturaja, South Sumatra Ogan Komering Ulu Regency, as an early warning before the Flavivirus outbreak. Research objective: This research was conducted to find out the larvae and mosquito species caught in the Sekarjaya sub-district of Ogan Komering Ulu Regency, South Sumatra, Indonesia. Method: mosquitoes use the odor sentinel trap method, in the morning (resting), animal-baited trap net, light trap. The research design was descriptive observational (field and laboratory). Results: this research showed that larval species were found in the study area in one survey, namely, Ae. aegypti, Ae. albopictus, Culex sp. and Armigeres sp. Species of mosquitoes found in the research area in one arrest are, Cx. tritaeniorhyncus, Cx. vishnui, Cx. gellidus, Cx. quinquefasciatus, Cx. nigropunctatus, Cx. whitei, Cx. fuscocephalus, Cx. hutchinsoni, Cx. bitaeniorhyncus, Cx. mimulus, An. vagus, An. barbirostris, An. tesselatus, An. nigerrimus, An. kochi, Ae. albopictus, Ae. vexans, Ae. aegypti, Aedes sp. and Ar. subalbatus. Keywords: Viruses, Flaviviridae, Larvae and Mosquitoes, Baturaja ABSTRAK Pendahuluan: data vektor dan penyakit dari famili Flaviviridae Kabupaten Ogan Komering Ulu Sumatera Selatan, Indonesia belum diketahui, sehingga dengan demikian perlu diketahui larva dan nyamuk yang terdapat di Sekarjaya Baturaja Kabupaten Ogan Komering Ulu Sumatera Selatan, sebagai upaya peringatan dini sebelum terjadinya outbreak Flavivirus. Tujuan Penelitian: ini dilakukan untuk mengetahui spesies larva dan nyamuk yang tertangkap di kelurahan Sekarjaya Kabupaten Ogan Komering Ulu Sumatera Selatan, Indonesia. Metode: nyamuk menggunakan metode odor sentinel trap, pagi hari (resting), animal-baited trap net, light trap. Desain penelitian adalah bersifat deskriptif observasional (lapangan dan laboratorium). Hasil: penelitian menunjukkan bahwa Species larva yang di temukan di wilayah penelitian dalam satu kali survei yaitu, Ae. Aegypti, Ae. Albopictus, Culex sp. dan Armigeres sp. Species nyamuk yang di temukan diwilayah penelitian dalam satu kali penangkapan yaitu, Cx.tritaeniorhyncus, Cx.vishnui, Cx.gellidus, Cx.quinquefasciatus, Cx.nigropunctatus, Cx.whitei, Cx.fuscocephalus, Cx.hutchinsoni, Cx.bitaeniorhyncus, Cx.mimulus, An.vagus, An.barbirostris, An.tesselatus, An.nigerrimus, An.kochi, Ae.albopictus, Ae.vexans, Ae.aegypti, Aedes sp. dan Ar.subalbatus. Kata Kunci: Virus, Flaviviridae, larva dan Nyamuk, Baturaja